A discourse analysis of instructions on making traditional dishes in English and Vietnamese - Nguyễn Thị Thành Phát (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The language of instructions is a very essential one which has its own characteristics that made it different from other languages. This study is an investigation into the instructions on making traditional dishes in English and Vietnamese. The descriptive and contrastive methods were employed to discover the layout patterns, syntactic features, lexical choices, and cohesive devices. Then based on the investigation results, this study found the similarities and differences between instructions on making traditional dishes in English and those in Vietnamese. In addition, the findings of this study were presented based on a survey of 10 instructions on making traditional dishes in English and other 10 ones in Vietnamese which were transcribed and collected from instruction videos on making traditional dishes of famous chefs. The study found the three main components in the layout patterns of instructions in both languages including the introduction, the process, and the summary. In an aspect of syntactic features, common types of sentences, imperative sentences, and passive sentences in both languages were analyzed. Regarding lexical choices, there were three typical themes in instructions in both languages analyzed consisting of words and expressions denoting quantity, words denoting kitchen utensils, and action verbs denoting activities. The study also found out the cohesive devices of the instructions of making traditional dishes in both languages containing grammatical devices including reference and conjunction as well as lexical devices consisting of repetition and synonym. Based on the results of analyzing and contrasting the instructions on making traditional dishes in English and Vietnamese, the study summarized and came to some conclusions and implications for teaching and learning language. Accordingly, it is hoped that this thesis can make theoretical and practical contributions to teaching and learning English and can be useful for those who are interested in how to cook traditional dishes.